Roosting Selection by Red and Blue Lory (Eos histrio Muller, 1776) in Karakelang Island North Sulawesi - Diah Irawati Dwi Arini; Satyawan Pudyatmoko; Erny Poedjirahajoe (Jurnal Penelitian Kehutanan Wallacea, 2017)
The Red and blue lory is an endemic parrot species from Talaud Islands, North Sulawesi. The use of existing resources is suspected that occurs of selection including the roosting trees. The research aims to identifying the characteristics of Red and Blue Lory roost tree and determining variables in its selection. We measured 14 variables to identify the characteristics and selection of roost tree. Mann-Whitney test, T-test, Chi-sqare test and Binary Logistic Regression were employed to analyze data. We detected 11 roost trees in study field, there are Gehe (Pometia coriacea Radkl) nine individual, Binsar (Ficus variegata) and Lawean (Sterculia sp) one individual. The Chi-square test identified five variables which related to roost tree selection, i.e; branch-free bole length, canopy diameter, canopy density and the number of trees around the roost tree on diameter 20 - 40 cm and > 41 cm. The Logistic regression analysis detected three variables that gave the most influence on roost tree selection, but branch-free bole length gave the most influence on roost tree selection.